Unravelling optical and X-ray properties of the disc-dominated intermediate polar IGR J15094-6649. Issue 4 (29th March 2023) - Joshi, Arti; Rawat, Nikita; Schwope, Axel; Pandey, J C; Scaringi, Simone; Sahu, D K; Rao, Srinivas M; Singh, Mridweeka
ABSTRACT: We present analyses of an Intermediate Polar, IGR J15094-6649, based on the archival optical data obtained from the Transiting Exoplanet Survey Satellite ( TESS ) and X-ray data obtained from the Suzaku, NuSTAR, and Neil Gehrels Swift Observatory ( Swift ). Present analysis confirms and refines the previously reported spin period of IGR J15094-6649 as 809.49584 ± 0.00075 s. Clear evidence of a beat period of 841.67376 ± 0.00082 s is found during the long-term TESS optical observations, which was not evident in the earlier studies. The dominance of X-ray and optical spin pulse unveils the disc-fed dominance accretion, however, the presence of an additional beat frequency indicates that part of the accreting material also flows along the magnetic field lines. The energy-dependent spin pulsations in the low (<10 keV) energy band are due to the photoelectric absorption in the accretion flow. However, the complex absorbers may be responsible to produce low amplitude spin modulations via Compton scattering in the hard (>10 keV) energy band and indicate that the height of the X-ray emitting region may be negligible. The observed double-humped X-ray profiles with a pronounced dip are indicative of the photoelectric absorption in the intervening accretion stream. Analysis of the X-ray spectra reveals the complexity of the X-ray emission, being composed of multitemperature plasma components with a soft excess, reflection, and suffers from strong absorption.